1974
DOI: 10.1002/art.1780170113
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐catalyzed thermal aggregation of human gamma‐globulin inhibition by histidine, gold thiomalate, and penicillamine

Abstract: Gold thiomalate (40 pM), penicillamine (40 pM), and histidine (20 pM) inhibit the copper-catalyzed (20 pM) thermal aggregation of human gamma globulin (0.8 mg/ml). At these concentrations, inhibition of gamma globulin aggregation was 87%, 96%, and 99% complete. This effect may be related to the reported suppressive effect of these agents in rheumatoid arthritis and adds support to the hypothesis that the hypohistidinemia of rheumatoid arthritis participates in the pathogenesis of the disease. Gold thiomalate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

1975
1975
1989
1989

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…It has been proposed that hypohistidinemia, because of an associated low synovial fluid histidine concentration (26), contributes to the pathogenesis of rheumatoid arthritis by permitting the sulfhydryl-dependent hyaluronate-augmented aggregation of synovial fluid gamma globulin, generating in the joint fluid an inflammatory and antigenic substance (aggregated gamma globulin) (27,28). The observations in the present study are consistent with this hypothesis.…”
Section: Methodssupporting
confidence: 90%
“…It has been proposed that hypohistidinemia, because of an associated low synovial fluid histidine concentration (26), contributes to the pathogenesis of rheumatoid arthritis by permitting the sulfhydryl-dependent hyaluronate-augmented aggregation of synovial fluid gamma globulin, generating in the joint fluid an inflammatory and antigenic substance (aggregated gamma globulin) (27,28). The observations in the present study are consistent with this hypothesis.…”
Section: Methodssupporting
confidence: 90%
“…Suggested mechanisms underlying the therapeutic efficacy ofthese drugs include the inhibition oflysosomal or other cellular enzymes (26)(27)(28), interference with complement activation (29,30), inhibition ofprostaglandin biosynthesis (31,32), alterations in protein interactions (33)(34)(35)(36) and sulfhydryl reactivity (37), and nonspecific antiinflammatory activity (38). It has also been suggested that they block the accessory cell functions of macrophages, leading to regression of cell-mediated immunological reactions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregated immunoglobulin was also the substance chosen in our experiments for generating chemotactic activity in plasma. Gerber (1971) has reported that gold thiomalate inhibited the heat aggregation of human gammaglobulin. In our experiments the gold salt was added to the plasma at the same time as the aggregated gammaglobulin and not during the gammaglobulin heating phase.…”
Section: Discussionmentioning
confidence: 99%